Conceptualizing entrepreneurial orientation and organizational performance of SME firms: organizational culture as antecedent and innovation management as Moderator / Sayuthi Shaaran, Ehsan Fansuree and Rohana Ngah - Shaaran, Sayuthi; Fransuree, Ehsan; Ngah, Rohana (2021)
The main purpose of this paper is to provide a conceptual framework on the role of entrepreneurial orientation in enhancing organizational performance in the context of small and medium-sized firms This paper is motivated by the ability of SME firms to interpret events and situations differently and to identify opportunities, and entrepreneurial orientation that are some of the characteristics that define a successful entrepreneurship. The understanding of how entrepreneurial orientation is embedded,can be fostered or impeded such orientation remain unanswered. Therefore, the antecedent variable and moderator variable are proposed. Based on entrepreneurial orientation literature and resource based-view theory, this paper proposes organizational culture as an antecedent to entrepreneurial orientation and innovation management as the moderator between entrepreneurial orientation and organizational performance. Additionally, the findings can be used for managerial practice.